The Effect of Baby Massage on The Quality of Babies 3-6 Month at Henny Clinik Tanjung Morawa Sub-Distric Deli Serdang Regency - Yatini; Shofi Saputri (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Optimal baby growth and development can be increased by meeting good nutritional needs, besides that another factor that can support this is by meeting the needs of adequate sleep for babies according to their age. Quality sleep for babies is sleep with regular frequency and also adequate sleep duration. In infants aged 0-12 months the duration of sleep needed by the baby is 12 to 17 hours including nap hours, this is very important to fulfill because the baby is still in the nocturnal period. One alternative option that can be done to improve sleep quality is to do baby massage or baby massage, baby massage can provide nerve stimulation to the baby's skin so that it can secrete out hormones that can provide drowsiness and comfort.this study used a pre-experimental design (Quasy experiment) with a one group pretest – post test design. The population in this study smelled 3-6 months old, sampling using total sampling techniques with a total sample of 25 babies. The results of the study using the Wilcoxon test showed that before massage was carried out on infants aged 3-6 months, the quality of sleep of infants in the sufficient category amounted to 12 respondents (48%) and after massage was carried out on infants aged 3-6 months, the quality of sleep of infants in the good category amounted to 17 respondents (68%). The results showed that there was an effect of baby massage on the sleep quality of infants aged 3-6 months at Henny Clinic, Tanjung Morawa District, with a significant value of p value = 0.000 <? (0.05). It can be concluded that baby massage has an effect on improving sleep quality in infants aged 3 - months at Henny Clinic, Tanjung Morawa District, Deli Serdang Regency. It is expected that parents can choose baby massage as an alternative non-pharmacological method in improving the quality of baby's sleep in order to achieve a more optimal degree of health and growth and development.